Odpowiedzi

Najlepsza Odpowiedź!
2009-11-20T00:16:10+01:00
2(x-3)+2x=x-3
2x -6 +2x = x -3
4x -6 = x -3
4x -x = -3 +6
3x = 3
x = 1
Odp. a, c,d

2(3-x)>3x
6 -2x > 3x
-2x -3x > -6
-5x > -6
x < 6/5
x< 1 i 1/5

Odp.b, c, d
  • Użytkownik Zadane
2009-11-20T00:21:14+01:00
1.2(x-3)+2x=x-3
2x - 6 + 2x = x - 3
4x - x = -3 + 6
3x = 3 /3
x = 1
odp. a. <1;3)

2.2(3-x)>3x
6 - 2x > 3x
-2x - 3x > -6
-5x > -6
x < 1,2
odp. b.
2009-11-20T00:23:40+01:00
1.Rozwiazaniem rownania 2(x-3)+2x=x-3
2x-6+2x=x-3
3x=3
x=1 pasuje a)c)d)
jest liczba z przedzialu : a. <1;3)
b. (-5;1)
c. <-3;3>
d. (0;5>
2.Do zbioru rozwiazan nierownosci 2(3-x)>3x
6-2x>3x
6>3x+2x
6>5x
x<1 i 1/5
b)c)d)
nalezy liczba:
a.2
b. 1
c. 0
d.-20